Gene Cloning and mRNA Expression of Glutamate Dehydrogenase in the Liver, Brain, and Intestine of the Swamp Eel, Monopterus albus (Zuiew), Exposed to Freshwater, Terrestrial Conditions, Environmental Ammonia, or Salinity Stress - Toh, C Y.; Chew, S. F.; Ip, Alex Y. (Frontiers in Physiology, 2011)
The swamp eel, Monopterus albus, is an obligatory air-breathing teleost which can survive long period of emersion, has high environmental and tissue ammonia tolerance, and acclimate from fresh to brackish water. This study was undertaken to clone and sequence gdh expressed in the liver, intestine and brain of M. albus, to verify whether more than one form of gdh were expressed, and to examine the gdh mRNA expressions in these three organs in fish exposed to various adverse conditions using quantitative real-time PCR. Only one gdh gene sequence, consisted of a 133 bp 5’ UTR, a CDS region spanning 1629 bp and a 3’ UTR of approximately 717 bp, was obtained from the liver, intestine and brain of M. albus. The translated Gdh amino acid sequence from the liver of M. albus had 542 residues and was confirmed to be Gdh1a. It had sequence identity of >90% with Oncorhynchus mykiss Gdh1a, Salmo salar Gdh1a1, Bostrychus sinensis Gdh1a and Tribolodon hakonensis Gdh1a, and formed a monophyletic clade with B. sinensis Gdh1a, Tetraodon nigroviridis Gdh1a, Chaenocephalus aceratus Gdh1a, Salmo salar Gdh1a1 and Gdh1a2 and O. mykiss Gdh1a. An increase in mRNA expression of gdh1a could be essential for increased glutamate production in support of increases in glutamine synthesis under certain environmental condition. Indeed, exposure of M. albus to 1 day of terrestrial conditions or 75 mmol l-1 NH4Cl, but not brackish water, resulted in a significant increase in gdh1a mRNA expression in the liver. However, exposure to brackish water, but not terrestrial conditions or 75 mmol l-1 NH4Cl, lead to a significant increase in the intestinal mRNA expression of gdh1a. By contrast, all the three experimental conditions had no significant effects on the mRNA expression of gdh1a in the brain of M. albus. Our results indicate for the first time that gdh mRNA expression was differentially up-regulated in the liver and intestine of M. albus, in responses to ammonia toxicity and salinity stress, res